Marginal seal evaluation of adhesive amalgam restaurations - Vučković Vesna 1; Jakovljević Ankica V.; Ivanović Vladimir (Serbian Medical Society - Dental Section, Belgrade, 2004)
Dental amalgam is still the material most commonly used to restore posterior teeth in many countries. Amalgam is very popular because of its strength, longevity, low cost, and relative ease of handling compared to other direct restorative materials. Two important disadvantages of amalgam restaurations are lack of adhesion to tooth structure and marginal leakage. Introduction of dentin adhesive systems enabled better marginal seal between amalgam and tooth structure. Aim: The aim of this study was to estimate, in vitro conditions, the marginal seal of amalgam restaurations with dentin adhesive systems using the method of diffusion dye. Material and methods: In this study 50 extracted human teeth were used. Class II cavities were prepared on all the teeth. The teeth were divided in five groups and materials applied according to manufacturer's instructions: Gamabond, Optibond Solo, OptiGuard, Ionosit - Base Liner and control group. All the teeth were thermocycled 200 times, at temperatures: 5 - 7ºC, 37ºC and 57 - 59ºC. Method of diffusion dye was used to estimate the quality of marginal seal of amalgam restaurations. All teeth were immersed into 50% solution of silver nitrate, and then into 10% developing solution. All teeth were cut with a diamond disc in the meso - distal plane. Penetration dye was estimated using binocular magnifying glass that magnifies 25 times, with inserted micrometar scale. Results were statistically analysed with Student t - test. Results: The least penetration dye was recorded in the group of amalgam restaurations rebonded with OptiGuard. Higher penetration dye was noted in the groups of adhesive amalgam restaurations, where Gamabond showed lower penetration dye in comparison with Optibond Solo. Penetration dye in the group Ionosit - Base Liner was higher than in the groups where dentin adhesive systems were used: on the occlusal wall, penetration dye in comparison with Gamabond showed statistically significant difference, (p < 0,5) while penetration dye in comparison with Optibond Solo showed no statistically significant difference. On the gingival wall, penetration dye in comparison with dentin adhesive systems - Gamabond and Optibond Solo, showed a statistically significant difference, (p < 0,01). The highest penetration dye was in the control group. Conclusion: The best marginal seal of amalgam restaurations was achieved with OptiGuard. Use of dentin adhesive systems also provided good marginal seal, with better results from Gamabond compared to Optibond Solo. Using Ionosit - Base Liner good marginal seal on the occlusal wall was also accomplished, while penetration dye on the gingival wall showed a statistically significant difference in comparison with adhesive and rebonding amalgam restaurations.